A systematic review of associations between physical activities and environmental factors among older adults in urban parks - Abd Shukor, Shureen Faris; Muthuveeran, Adam Aruldewan S.; Maulan, Suhardi; Chen, Yurui (UPM Press, 2025)
With the escalating global trend of population ageing, urban parks are increasingly recognized as pivotal spaces for leisure activities among older adults. Comprehensive reviews focusing on older adults’ activities in urban parks, along with the pertinent environmental factors, remain scarce. This paper provides an in-depth study of the literature on older adult's activity patterns in urban parks and the environmental factors that influence their activities. A systematic search was conducted using keywords in reputed databases such as SCOPUS and WoS, resulting in the review of 85 papers, which were subsequently analysed thematically using ATLAS.TI software. Research trends can be categorised into health indicators, proximity and psychosocial factors from 2003 to 2024. The most common activity that older adults engage in is walking, and park design factors such as path width, vegetation cover and pet-friendliness significantly influence their walking behaviour. In addition, older adults' physical activity is not only influenced by the physical environment but also by psychosocial factors, showing geographic and gender differences. Older adults' motivations for using parks include thermal comfort, meaning of place, and social interaction, factors that are strongly associated with their physical and mental recovery, and well-being. Future research should further explore the specific mechanisms at play between environmental factors and physical activity among older adults, with attention to differences across cultural contexts, to provide a more comprehensive guide to the design of urban parks.